The effect of stem cell therapy and comprehensive physical therapy in motor and non-motor symptoms in patients with multiple sclerosis: A comparative study. Issue 34 (21st August 2020) - Alghwiri, Alia A.; Jamali, Fatima; Aldughmi, Mayis; Khalil, Hanan; Al-Sharman, Alham; Alhattab, Dana; Al-Radaideh, Ali; Awidi, Abdalla
Abstract: Introduction: People with multiple sclerosis (PwMS) experience a wide range of disabilities which negatively impact their quality of life (QOL). Several interventions have been used in PwMS such as medication, physical therapy exercises and stem cell therapy to improve their QOL. However, there is a limited evidence on the benefits of combining interventions. The purpose of this study is to explore the effect of combining physical therapy exercises (PTE) and Wharton Jelly mesenchymal stem cell (WJ-MSCs) injections on motor and non-motor symptoms versus each intervention alone in PwMS. Methods: Sixty PwMS will be allocated to either PTE, WJ-MSCs, or a combined group, followed up for 12 months and examined using a comprehensive battery of measures. Participants in the PTE group will receive 2 sessions per week of a supervised exercise program for 6 months followed by a home exercise program for another 6 months. The WJ-MSCs group will receive 3 WJ-MSCs injections in the first 6 months then they will be encouraged to follow an active life style. The third group will receive both interventions. Discussion: This study will aid in a better understanding of the combined effect of physical therapy and mesenchymal stem cell therapy. The results from this proposed study may reduce disability, improve QOL in PwMS, and consequently, reduce the cost associated with the life-time care of these individuals worldwide. Trial registration number: NCT03326505 Abstract : Supplemental Digital Content is available in the text